1970
DOI: 10.3329/jom.v11i2.5474
|View full text |Cite
|
Sign up to set email alerts
|

An Old Man with Unusual Precordial Pain

Abstract: We describe an interesting case of unusual origin of precordial pain. A 75-year-old man was admitted to theEmergency Room of José Frota Institute, Fortaleza city, Brazil, because of precordial pain and malaise, three daysafter eating a bread. Physical examination was unremarkable. The electrocardiogram showed diffuse upward STsegment.A chest radiography showed a foreign body (a pin) in the topography of the esophagus. Esophagoscopywas performed and the pin was removed, with improvement of the patient.Keywords:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…It is important to emphasize that in this study the increase in BD did not influence Ma reduction, such as it is usually observed (Silva et al 2014;Auler et al 2017). This behavior might be a consequence of biopores formation, influenced by the increase in the earthworm activity or at root growth conditioned by liming (Caires et al 2008;Joris et al 2013;Auler et al 2017).…”
Section: Liming Effects In the Soil-water-air Relationsmentioning
confidence: 84%
See 1 more Smart Citation
“…It is important to emphasize that in this study the increase in BD did not influence Ma reduction, such as it is usually observed (Silva et al 2014;Auler et al 2017). This behavior might be a consequence of biopores formation, influenced by the increase in the earthworm activity or at root growth conditioned by liming (Caires et al 2008;Joris et al 2013;Auler et al 2017).…”
Section: Liming Effects In the Soil-water-air Relationsmentioning
confidence: 84%
“…That result might be explained due to the importance of the macropores for the soil aeration (Silva et al 2014).…”
Section: Liming Effects In the Soil-water-air Relationsmentioning
confidence: 97%